Looking towards objective quality evaluation in colonoscopy: Analysis of visual gaze patterns. Issue 3 (26th February 2016) - Edmondson, Matthew J; Pucher, Philip H; Sriskandarajah, Kumuthan; Hoare, Jonathan; Teare, Julian; Yang, Guang‐Zhong; Darzi, Ara; Sodergren, Mikael H
Abstract: Background and Aim: There are currently limited training and assessment tools available to novice endoscopists. A potential tool for the objective assessment of endoscopist visual search strategy is eye‐tracking technology. The aim of this study is to assess whether eye‐tracking technology can be used to differentiate the visual gaze patterns (VGP) of experienced and novice endoscopists, and to characterize any differences arising between the two groups. Method: With the use of portable eye‐tracking glasses, VGP of novice ( n = 20) and experienced ( n = 14) endoscopists were compared while viewing a colonoscopy withdrawal through the hepatic flexure. Analysis was performed by comparing the central versus peripheral distribution and the horizontal distribution of novice and experienced endoscopist fixations, along with comparison of basic eye‐tracking metrics. Results: This study found that experienced endoscopists had a significantly higher percentage of fixations within the periphery of the screen (13.4% vs 23.0%, P = 0.013). Experienced endoscopists also had a significantly greater percentage of fixations on the left side of the screen (18.6% vs 33.5%, P = 0.005) that displayed the poorly visualized "inside bend" of the hepatic flexure. Conclusion: This study has detailed specific VGP acquired through expertise, which can potentially explain why adenomas are regularly missed at the hepatic flexure during colonoscopy. These may be useful for the training of novice colonoscopists, and further validation may utilize VGP in the development of an objective proficiency based curriculum to improve the detection of pathology and overall quality in endoscopy.